Developing Novel Host-Based Therapies Targeting Microbicidal Responses in Macrophages and Neutrophils to Combat Bacterial Antimicrobial Resistance - Watson, Katie; Russell, Clark D.; Baillie, J. Kenneth; Dhaliwal, Kev; Fitzgerald, J. Ross; Mitchell, Timothy J.; Simpson, A. John; Renshaw, Stephen A.; Dockrell, David H. (Frontiers in Immunology, 2020)
Antimicrobial therapy has provided the main component of chemotherapy against bacterial pathogens. The effectiveness of this strategy has, however, been increasingly challenged by the emergence of antimicrobial resistance which now threatens the sustained utility of this approach. Humans and animals are constantly exposed to bacteria and have developed effective strategies to control pathogens involving innate and adaptive immune responses. Impaired pathogen handling by the innate immune system is a key determinant of susceptibility to bacterial infection. However, the essential components of this response, specifically those which are amenable to re-calibration to improve host defense, remain elusive despite extensive research. We provide a mini-review focusing on therapeutic targeting of microbicidal responses in macrophages and neutrophils to de-stress reliance on antimicrobial therapy. We highlight pre-clinical and clinical data pointing towards potential targets and therapies. We suggest that developing focused host-directed therapeutic strategies to enhance ‘pauci-inflammatory’ microbial killing in myeloid phagocytes that maximizes pathogen clearance while minimizing the harmful consequences of the inflammatory response merits particular attention. We also suggest the importance of One Health approaches in developing host-based approaches though model development and comparative medicine in informing our understanding of how to deliver this strategy.while minimizing the harmful consequences of the inflammatory response merits particular attention. We also suggest the importance of One Health approaches in developing host-based approaches though model development and comparative medicine in informing our understanding of how to deliver this strategy.